Implementation of Mind Mapping in Social Studies Subjects on Socio-Cultural Changes for Junior High School Students - Armawati Hidayati; Faridatul Lailiyah; Ana Hidayati (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The purpose of this research is to: (1) Describe the implementation of the mind mapping method, and (2) Describe the improvement of activities and learning outcomes in Social Studies (IPS). This research adopts a classroom action research (CAR) design. Based on the results of the classroom action research aimed at improving the process and learning outcomes of students, the following conclusions can be drawn: (1) The implementation of the mind mapping method in Social Studies for Grade IX students at SMPN 7 Bojonegoro involves several stages: (a) Ensure that the main theme is placed in the middle, (b) From the main theme, determine the main branches that are still related to the main theme, (c) Determine sub-topics as